Contributions of the Humanities in the training of the Surgeon of the University of Antofagasta - Torres Belma, Alberto; Varas Varas, Diego (Spanish Journal of Medical Education, 2024)
If the teaching of Medicine is a great challenge for any health professional, the challenge will be greater for a professional in charge of this and belonging to the area of the humanities. It is here where the discipline of Psychopedagogy gains strength, supporting both teachers and students, becoming a holistic support that, within the possibilities, positively influences both the professional and personal training of the future doctor.